2021
DOI: 10.1007/s00018-020-03731-4
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear organization and regulation of the differentiated state

Abstract: Regulation of the differentiated identity requires active and continued supervision. Inability to maintain the differentiated state is a hallmark of aging and aging-related disease. To maintain cellular identity, a network of nuclear regulators is devoted to silencing previous and non-relevant gene programs. This network involves transcription factors, epigenetic regulators, and the localization of silent genes to heterochromatin. Together, identity supervisors mold and maintain the unique nuclear environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 179 publications
(219 reference statements)
0
14
0
Order By: Relevance
“…Conversely, and perhaps more surprisingly, when these same cells were placed on soft substrates, highly condensed chromatin domains relocalized to the nuclear periphery, a region in which constitutive heterochromatin resides and methyltransferases are abundant 16,29 . This nuclear periphery has long been considered as a transcriptionally repressive area 40 where inner nuclear membrane proteins in the nuclear lamina interact with proximal chromatin creating heterochromatin structures 41,42 . It has recently been suggested that this laminal sequestration at the nuclear envelope depends on specific epigenetic modifications, and indeed we observed that human MSCs on soft substrates increased their nano-scale H3K27me3 localization at the nuclear periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, and perhaps more surprisingly, when these same cells were placed on soft substrates, highly condensed chromatin domains relocalized to the nuclear periphery, a region in which constitutive heterochromatin resides and methyltransferases are abundant 16,29 . This nuclear periphery has long been considered as a transcriptionally repressive area 40 where inner nuclear membrane proteins in the nuclear lamina interact with proximal chromatin creating heterochromatin structures 41,42 . It has recently been suggested that this laminal sequestration at the nuclear envelope depends on specific epigenetic modifications, and indeed we observed that human MSCs on soft substrates increased their nano-scale H3K27me3 localization at the nuclear periphery.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, genes required for specific differentiation are activated via detachment of genome regions from the nuclear lamina. These genome reorganizations are cell cycle stage-dependent, and vary in the different cells from different origins ( Bitman-Lotan and Orian, 2021 ; Shah et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that heterochromatin is associated with lamin A/C forming the nuclear lamina, while euchromatin dominating in the nuclear interior is connected with a small number of nucleoplasmic lamin A/C. A-type lamins are considered to regulate the repressive state of genes included in facultative heterochromatin ( Gruenbaum and Foisner, 2015 ; de Leeuw et al, 2018 ; Bitman-Lotan and Orian, 2021 ). This three-dimensional organization of chromatin contributes to the gene expression regulation and maintenance of silencing of heterochromatic genes.…”
Section: Lamin A/c As Tissue-specific Regulator Of Cell Differentiationmentioning
confidence: 99%
See 2 more Smart Citations